Drug Resistant Focal Epilepsy: Correlation between Ictal and Inter-ictal EEG Monitoring - Shaheen, Yara Salah; Elnaggar, Walaa; Elantably , Ismail; Elhabashy, Hala R.; Ali, Bassant Ibrahim; Fahmy Girgis, Marian Yousry (Journal of Neonatal Surgery, 2025)
Background: Video EEG is the gold-standard investigation to assess Ictal and Inter-ictal epileptiform brain activity Objective: To assess the concordance between ictal vs. inter-ictal Video-EEG during their pre-surgical evaluation. Methodology: In this observational cohort study, we involved Thirty children and adolescents with focal drug-resistant epilepsy who presented to the neuro-pediatric Cairo University children hospital clinics. All of them were submitted to history taking, full examination and 6–24-h long-term Video EEG recording (including ictal and inter-ictal recordings). Results: Analysis of long-term video EEG recordings showed that the ictal onset zone (IOZ) was right-sided in 50% of patients, left-sided in 43.3%, and bilateral in 6.7%. The IOZ was localized to the frontal lobe in 33.3%, temporal lobe in 30%, parietal lobe in 6.7%, and was multifocal in 30% of cases. Comparison between ictal and interictal EEG revealed no statistically significant differences in either lateralization (p = 0.964) or lobar localization (p = 0.126), indicating strong concordance between the two. Conclusion: In patients with focal drug-resistant epilepsy (DRE), long-term video-EEG data showed strong concordance between the ictal onset zone (IOZ) and interictal focal paroxysmal discharges. This suggests that ictal EEG contributes limited additional value to presurgical evaluation. Clinically, this could reduce the need for inpatient IOZ localization, thereby decreasing the costs, time, and resources associated with long-term video-EEG monitoring.